Privacy: right to private life under civil law (A Comparative Study between the Laws in United Kingdom and Malaysia) / Nur Azhar Bujang and Mohd Raimi Mohd Ramli. - Bujang, Nur Azhar; Mohd Ramli, Mohd Raimi (2008)
This research concerns about the right to privacy especially the right to a private life, the right to a private life which is stated in Article 12 of the United Nation Universal Declaration of Human Rights means the right to have a personal life, moral, physical integrity, personal identity, personal information, personal sexuality and personal or private space. Article 12 states that no one shall be subjected to arbitrary interference with his privacy, family, home or correspondence, or to attacks upon his honour and reputation. The absence of a specific provision regarding the matter of private life in Malaysia has caused several problems to the public which include the invasion of privacy of a person, the legislation of law which is regarded as oppressive which violates the right to a private life and the uncertainties in determining a person's right to a private life. This research will focus on the need for a legislation of a specific law to protect the right of a person to a private life in Malaysia.